Water resources in the Asia-Pacific region: managing scarcity - Rosegrant, Mark W.; Meinzen-Dick, Ruth S. (Wiley, 1996)
Irrigation, together with improved crop varieties and substantial growth in fertiliser use in the late 1960s through the early 1980s, was a key factor in stimulating strong agricultural growth in much of the Asia‐Pacific region. New sources of water are increasingly expensive to exploit, but irrigation continues to be a major catalyst for agricultural growth. In the face of increasing degradation, the maintenance of the water resource base must be a high priority policy objective. This paper reviews the management of water resources in the Asia‐Pacific region, for countries with significant irrigated area: Cambodia, China, Indonesia, Korea‐DPR, Republic of Korea, Laos, Malaysia, Mongolia, Myanmar, Philippines, Thailand and Vietnam.